Scientometric, social network scientographic analysis industrial engineering department. - Mathias Dharmawirya. (2008)
This dissertation examines the twenty-year publication output (from 1986 to 2005) of the National University of Singapore Industrial Engineering Department (NUS-ISE) based on three perspectives namely scientometrics, social network analysis, and multidimensional scaling.